Postharvest life of gladiolus cv. Candyman as influenced by locally available preservatives - Jangyukala, M; Hemanta, Laishram; Keditsu, Roholhuü; Keditsu, Roholhuü; Alila, Pauline; Sarkar, Animesh; Maiti, C S; Kanaujia, S P; Sema, Akali; Jamir, Sentirenla; Yepthomi, Graceli; Rahman M, Abdul; et al. (Journal of Postharvest Technology, 2024)
The investigation was conducted to determine the effect of locally available preservatives on vase life of gladiolus (Gladiolus grandiflora L.) cv.  Candyman flower. The economic value of cut flowers is dependent on their shelf life and the use of locally available floral preservatives is the  best cost efficient post-harvest method to preserve the longevity of the cut flowers. Cut gladiolus flowers were placed in 500 ml bottles containing  300 ml aqueous solution of various preservatives and distilled water as control was prepared. The vase solution containing citric acid 0.05% +  cane sugar 2% + commercial bleaching powder 0.005% had the minimum number of days to basal floret opening, maximum basal floret size  and also recorded the longest total blooming period and vase life of 9.60 and 7.60 days, respectively. On the other hand, use of commercial  bleaching powder 0.005% as a locally available vase life preservative was economically more capable to extend the vase life of gladiolus as the  benefit cost returns were recorded to be the highest (3.60) in this treatment. Therefore, the study recommends the use of commercial bleaching  powder 0.005% as an ideal vase life concentration for the vase life of gladiolus cv. Candyman.
Keywords: Commercial bleaching powder; economical; gladiolus; local; post-harvest